Трипільська археологічна культура в Україні - Відейко, М. (Народна творчість та етнографія, 2005)
Among reach archeological heritage of Ukraine special place takes Trypillya culture which is traditionally connected to the creation of the first civilization of Ukrainians. The period of the existence of the Trypillya culture is more then 2500 years. It means than in the time frames of the lengths of its existence this culture does not yield to other civilizations. The approximate chronology of the Trypillya culture is tightly connected to the archeological monuments.